Simulation investigation on impact damage characteristics of metal plate by cavitating bubble micro-jet water hammer. (September 2020) - Xie, Zhanshan; Shi, Weidong; Zheng, Yuan; Tan, Linwei; Tian, Qian; Cao, Yupeng; Zhou, Jingling; Ge, Xinfeng
Highlights: Micro-jets perpendicularly hammering the material cause the greatest damage to the material surface and generate the eccentric bowl-shaped erosion pit are given. The magnitude of material surface stress is positively related to the velocity of water hammer, the surface stress in the hammering area is the largest, and the stress nephogram is conical. Neglecting the damage at the end of hammering, the surface of the material produced the maximum stress at the moment when the micro-jets contact the metal plate, and the magnitude of stress decreases with the impact process. Abstract: In order to obtain the fatigue damage characteristics of materials from the cavitation bubble collapse zone, a hammering strategy of micro-jet water hammer is conceived, and a hammering of metal plate by micro-jet water hammer with cavitation bubbles is studied by numerical simulation method. The stress response characteristics of the metal plate(HT-200) in the instantaneous and whole hammering process are explored. It is also revealed that the maximum stress will be generated when water hammer with the same velocity hammering the metal plate at 90 degrees angle, and a bowl-shaped impact will be formed. However, eccentric bowl-shaped pit will be produced when the metal plate is hammered at a non-90 degree angle. Meanwhile, the simulation results are compared with the experimental cavitation pits, and the validity of the numerical simulation is verified.